2004
DOI: 10.1645/ge-237r
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Swimmer's Itch Incidence and Severity

Abstract: This epidemiologic study reports incidence, severity, and risk factors of swimmer's itch (cercarial dermatitis). Daily diaries about water exposures and swimmer's itch symptoms were completed by 40 riparian households at Douglas Lake, Michigan, for July 2000. Minutes spent in the water, minutes in shallow water, location, time of day, preventive action, age, and gender were recorded for all residents and guests. Incidence of swimmer's itch was 6.8 episodes per 100 water-exposure days. Probability of an episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…Cercarial dermatitis develops as a result of sensitization of the human immune system (232,260), and repeated exposures to cercariae influence the occurrence and intensity of subsequent infections. For example, longer exposure in water increases cercarial penetration via frequent water visits and more time spent in shallow water (4,(304)(305)(306). While gender does not influence the risk of infection (4,304,305,307), some studies found a higher risk among children of less than 15 years of age, since they tend to spend more time in shallow water (280,308,309).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
See 3 more Smart Citations
“…Cercarial dermatitis develops as a result of sensitization of the human immune system (232,260), and repeated exposures to cercariae influence the occurrence and intensity of subsequent infections. For example, longer exposure in water increases cercarial penetration via frequent water visits and more time spent in shallow water (4,(304)(305)(306). While gender does not influence the risk of infection (4,304,305,307), some studies found a higher risk among children of less than 15 years of age, since they tend to spend more time in shallow water (280,308,309).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
“…For example, longer exposure in water increases cercarial penetration via frequent water visits and more time spent in shallow water (4,(304)(305)(306). While gender does not influence the risk of infection (4,304,305,307), some studies found a higher risk among children of less than 15 years of age, since they tend to spend more time in shallow water (280,308,309). There are rare cases of nonsensitive individuals that may be due to host desensitization (310) or individual nonsusceptibility/nonattractivity to cercariae (4,311).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that our knowledge about human incidence and risk factors is rather limited in Central Europe [12] and even in the world [13][14][15], a website [16] was created in spring 2003 with information for persons concerned, combined with the option to download a questionnaire to provide us with first-hand information.…”
Section: Introductionmentioning
confidence: 99%